Progesterone for the prevention of preterm birth: indications, when to initiate, efficacy and safety - Helen Y How; Baha M Sibai (Dove Medical Press, 2008)
Helen Y How, Baha M SibaiDivision of Maternal Fetal Medicine, Department of Obstetrics and Gynecology, University of Cincinnati, Cincinnati, OH USAAbstract: Preterm birth is the leading cause of neonatal mortality and morbidity and long-term disability of non-anomalous infants. Previous studies have identified a prior early spontaneous preterm birth as the risk factor with the highest predictive value for recurrence. Two recent double blind randomized placebo controlled trials reported lower preterm birth rate with the use of either intramuscular 17 alpha-hydroxyprogesterone caproate (IM 17OHP-C) or intravaginal micronized progesterone suppositories in women at risk for preterm delivery. However, it is still unclear which high-risk women would truly benefit from this treatment in a general clinical setting and whether socio-cultural, racial and genetic differences play a role in patient’s response to supplemental progesterone. In addition the patient’s acceptance of such recommendation is also in question. More research is still required on identification of at risk group, the optimal gestational age at initiation, mode of administration, dose of progesterone and long-term safety.Keywords: preterm birth prevention, 17-alpha-hydroxyprogesterone caproate